Transcriptome analysis reveals the immunoregulatory effect of two polysaccharides from Rhodomyrtus tomentosa - Li, Dingjin; Duan, Qiuxia; Wan Ibadullah, Wan Zunairah; Shukri, Radhiah; Nie, Hui; Ren, Aiqing; Mustapha, Nor Afizah (Multidisciplinary Digital Publishing Institute (MDPI), 2026)
The Rhodomyrtus tomentosa (Aiton.) Hassk. berry is rich in structurally diverse polysaccharides with potential biological activity. However, its immunomodulatory properties remain understudied, limiting our current understanding of its functional significance. Two structurally distinct polysaccharides from Rhodomyrtus tomentosa (RTP-1 and RTP-2) were evaluated for immunostimulatory activity in RAW264.7 macrophages. Phagocytic function was assessed by neutral red assay, nitric oxide (NO) and reactive oxygen species were measured using the Griess assay and fluorescent probes, and cytokines (TNF-α, IL-6 and IL-1β) were quantified by enzyme-linked immunosorbent assay. Analysis of RNA-seq data using weighted gene co-expression network analysis revealed co-expression modules. The selected transcripts were independently validated by quantitative real-time PCR (RT-qPCR). The results showed that both polysaccharides enhanced phagocytosis, increased NO/ROS levels, and promoted cytokine secretion. Transcriptome results indicated that RTP-2 activated the MEturquoise co-expression module containing 222 hub genes, whereas RTP-1 was mainly associated with the MECyan module containing 49 hub genes. Module enrichment for RTP-2 revealed links with mitophagy–immune regulation, proteostasis/stress, and innate immune signaling. RT-qPCR further confirmed that in the RTP-2 group, Dram1 expression was upregulated approximately 121 times, Bmf1 expression was upregulated approximately 18 times, and Bnip3 was significantly downregulated, whereas Bnip3l expression remained unchanged. Overall, RTP-2 exhibited a more pronounced and coherent macrophage-stimulating profile in vitro, supporting its potential as a macrophage-targeted immunostimulatory ingredient.